Erratum to: Closed Die Deformation Behavior of Cylindrical Iron–Alumina Metal Matrix Composites During Cold Sinter Forging (Journal of The Institution of Engineers (India): Series D, (2016), 97, 2, (135-151), 10.1007/s40033-015-0089-1) - Kumar U.J.P.; Gupta P.; Jha A.K.; Kumar D. (My University, 2025)
Under the subheading ‘Preparation of Composite Samples’, at line no. 3, powder to ball ratio ‘2:1’ was wrongly printed in the original publication of this article. The correct powder to ball ratio should be ‘1:2’. © The Institution of Engineers (India) 2016.